The Interpretation of Qs Al-Mujadalah [58]: 11 on Knowledge and Faith According to Fakhruddin Al-Razi and Muhammad Izzat Darwazah - Fatimah Az Zahra; Ahmad Nurrahim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The study of knowledge and faith in Islam holds great urgency, especially in understanding how both serve as key factors in elevating a Muslim’s rank. Surah Al-Mujadalah [58]:11 affirms that Allah raises the ranks of those who believe and those endowed with knowledge. This study aims to examine the interpretation of the verse from the perspectives of Fakhruddin al-Razi in Mafatih al-Ghaib and Muhammad Izzat Darwazah in At-Tafsir al-Hadith, in order to understand the meaning of believers and the knowledgeable, as well as the concept of “ascending in rank in the sight of Allah” as explained in classical and modern exegesis. This research employs a comparative method through a library research approach. The results show that both al-Razi and Darwazah agree that faith is not merely verbal acknowledgment, but must be realized through concrete actions. However, al-Razi emphasizes the hierarchical relationship between knowledge and levels of faith, where deeper knowledge leads to higher spiritual attainment. Meanwhile, Darwazah highlights the social dimension of faith and knowledge through ethics, manners, and social practice in communal life. These differences indicate that classical and modern exegesis possess distinct interpretative orientations in understanding the relationship between knowledge and faith in QS Al-Mujadalah [58]: 11.